PELAKSANAAN PASAL 74 UNDANG-UNDANG 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS TERHADAP KASUS TELUK BUYAT DI INDONESIA - Lestari, Sartika Nanda (Fakultas Hukum, Universitas Diponegoro, 2017)
Corporate social responsibility is interpreted as a continuous commitment by the business to act ethically and contribute to the development of the economy and the local community or the wider community. Indonesia is one of the countries that realize the importance of corporate social responsibility, that is, with the regulation of corporate social responsibility in Article 74 Company Act No. 40/2007. In the case of Buyat Bay in Indonesia, there is still a different understanding of corporate social responsibility. This is due to the absence of arrangements in detail to explain the form of corporate social responsibility that must be done by the company. Keywords : Article 74, company, corporate social responsibility